2022
DOI: 10.3389/fimmu.2022.963582
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL1R1 or CASP4 attenuates spinal cord injury through ameliorating NLRP3 inflammasome-induced pyroptosis

Abstract: Spinal cord injury (SCI) is a devastating trauma characterized by serious neuroinflammation and permanent neurological dysfunction. However, the molecular mechanism of SCI remains unclear, and few effective medical therapies are available at present. In this study, multiple bioinformatics methods were used to screen out novel targets for SCI, and the mechanism of these candidates during the progression of neuroinflammation as well as the therapeutic effects were both verified in a rat model of traumatic SCI. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…SCI is recognized to be accompanied by heightened oxidative stress and activation of the inflammasome NLRP3, leading to the cleavage and release of pro-IL-18/1β and consequent initiation of a potent inflammatory response [31]. Recent research has demonstrated that the inhibition of pyroptosis can effectively alleviate motor dysfunction resulting from SCI [32]. Macrophage/microglia are intrinsic immune cells in the CNS, and numerous studies have shown that macrophage/microglia pyroptosis plays an important role in the development of neuroinflammation [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…SCI is recognized to be accompanied by heightened oxidative stress and activation of the inflammasome NLRP3, leading to the cleavage and release of pro-IL-18/1β and consequent initiation of a potent inflammatory response [31]. Recent research has demonstrated that the inhibition of pyroptosis can effectively alleviate motor dysfunction resulting from SCI [32]. Macrophage/microglia are intrinsic immune cells in the CNS, and numerous studies have shown that macrophage/microglia pyroptosis plays an important role in the development of neuroinflammation [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the involvement of the NF-κB/NLRP3 inflammasome signaling pathway in regulating pyroptosis in various diseases, such as spinal cord injury [ 46 ], diabetic cardiomyopathy [ 47 ] and Aspergillus fumigatus keratitis [ 48 ]. In this study, KEGG analysis of differentially expressed genes in TB patients’ peripheral blood transcripts revealed a significant enrichment of the NOD-like receptor (NLR) signaling pathway, NF-κB signaling pathway, and other inflammation-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…IGSF6 is a novel member of the immunoglobulin superfamily, which belongs to the CD8 family of receptors and perhaps functions as a co-receptor [ 19 ]. The IGSF6 gene has been identified as a candidate for susceptibility to various diseases [ 31 , 32 ]. However, its role in immune engagement during LUAD is not well understood.…”
Section: Discussionmentioning
confidence: 99%